Participation of Stanisław Tomkowicz in the conservation of the Corpus Christi collegiate church in Biecz - Czubiński, Jacek (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2017)
The collegiate parish church in Biecz is an outstanding example of Gothic architecture. In the second half of the nineteenth century, he carried out restoration work, what in 1887−1895 was supervised by the conservator of the Vienna Central Commission, Stanisław Tomkowicz. The article presents his participation in the preservation of the church. Sławomir Odrzywolski was the author of the conservation project. Tomkowicz’s influence on design decisions as well as the scope and manner of conducted works was presented. An attempt was made to determine the conservation me thod in relation to prevailing tendencies in protection of monuments, moving away from the trend of a stylistic restauration in favor of strict conservation.